Pipeline embolization devices for the treatment of nonsaccular aneurysms in pediatric patients - Han, Jintao; Liang, Fei; Zhang, Yuxiang; Zhang, Yupeng; Liang, Shikai; Zhu, Haoyu; Chang, Yuzhou; Ma, Chao; Liu, Lian; Jia, Zichang; Jiang, Chuhan (Frontiers in Neurology, 2023)
Objective Pediatric nonsaccular aneurysms are rare but challenging lesions; pipeline embolization devices (PEDs) are their potential treatment option. In this study, we aimed to evaluate the safety and efficacy of PEDs for treatment of these aneurysms. Methods We retrospectively selected pediatric patients with nonsaccular aneurysms treated using PEDs between June 2015 and July 2021 from our prospectively maintained database. For each patient, demographics, aneurysm characteristics, procedure details, and clinical and angiographic follow-up data were collected and summarized. Results This study included 16 pediatric patients with 16 nonsaccular aneurysms treated with PEDs. A median clinical follow-up time of 1,376 days was achieved in 93.75% of the patients. The complication rate of the included patients was 25%, with two patients developing mass effect, one patient undergoing major ischemic stroke, and one patient experiencing stent foreshortening after the procedure. The complete occlusion rate of aneurysms without any neurologic sequelae was 93.33%, with a median angiographic follow-up period of 246 days. The mortality rate was 6.25%. Conclusions The use of PEDs to treat pediatric nonsaccular aneurysms is feasible, with a high rate of complete occlusion of the aneurysm and favorable follow-up outcomes.